Who took our cake? (nelson focus) - Hammonds, Heather (Nelson Thomson Learning South Melbourne, Vic., 2001)
"Who Took Our Cake?" is a delightful children's story centered around a group of friends who discover that their cake has mysteriously disappeared. As they embark on a playful investigation, they question each other and various characters to uncover the truth. The narrative is filled with humor, suspense, and teamwork as the friends work together to solve the mystery.